STX2 Promotes Trophoblast Growth, Migration, and Invasion Through Activation of the PI3K-AKT Pathway in Preeclampsia - Li, Yan; Sun, Xian-li; Ma, Chun-ling; Li, Chao; Zhan, Ying; Li, Wen-ting; Li, Can; Wang, Yi-hao (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Abnormal Trophoblast behaviors during pregnancy contribute to the development of preeclampsia (PE). Syntaxin2 (STX2) has been found to be a crucial epithelial mediator in numerous diseases, with its roles and mechanisms largely undetermined in PE. This study was conducted to explore the role of STX2 on trophoblast and the underlying mechanism. Materials and Methods: We first compared STX2 expression in placenta from PE patients and normal pregnancies. Then we explored the role of STX2 on cell proliferation, migration and invasion in different trophoblasts by loss or gain function of experiments. In addition, Co-immunoprecipitation (Co-IP) and immunofluorescence (IF) co-localization assays were performed to evaluated the underlying mechanism of STX2-mediated trophoblasts functions. Results: We demonstrated that STX2 expression was downregulated in PE patients’ placenta compared with those from normal pregnancies. Moreover, loss or gain function of experiments confirmed that STX2 advanced cell proliferation, migration and invasion in trophoblasts. By Co-immunoprecipitation (Co-IP) and immunofluorescence (IF) co-localization approaches, we revealed that STX2 selectively interacted with p85, a subunit of PI3K, directly recruited the latter to the cytomembrane and thus activated the AKT signaling pathway. We further demonstrated that the activation of AKT abolished by PI3K inhibitor LY294002 affected STX2-mediated trophoblasts functions. Conclusion: Collectively, our work illustrates that STX2 is a crucial modulator in PE progression and highlights that STX2 could be a potential diagnostic biological indicator and therapeutic target in treating PE patients.